GERMINATION AND VIGOR OF Bixa orellana L. SEEDS PRE-SOAKED IN A PLANT BIOSTIMULANT - Araujo Neto, Aderson Costa; dos Santos, Olívia Oliveira; Ferreira, Darlaine Maria; Nunes, Renan Thiago Carneiro; Públio, Ana Paula Prado Barreto; Amaral, Cláudio Lúcio Fernandes (Floresta, 2018)
The aim of this study was to assess the germination and vigor of Bixa orellana seeds that were pre-soaked in different concentrations of Stimulate® plant biostimulant. For the standard germination test, Bixa orellana seeds from the Embrapa 37 Cultivar were pre-soaked (for periods of four and eight hours) in the following concentrations of Stimulate® aqueous solution: 3.0; 6.0; 9.0; and 12.0 mL L-1. Seeds that were pre-soaked in distilled water were used as control. The following parameters were tested: germination; first germination count; abnormal seedlings; length; and seedling dry mass. The experimental design was completely randomized and a 2 x 5 + 1 factorial design was used (with two pre-soaking periods, five Stimulate® concentrations, and one additional control without pre-soaking). Four replicates of 50 seeds were performed for each treatment. Water immersion treatments for four and eight hours were efficient for breaking dormancy in Bixa orellana seeds, since they promoted better germination in relation to the intact seeds that were not pre-soaked. The pre-soaking of Bixa orellana seeds for eight hours in a 12.0 mL L-1 Stimulate® concentration presented the best results in terms of germinative performance and seedling growth, with greater accumulation of dry mass. Therefore, this practice is recommended for the production of seedlings of this species.